"A Widespread Loss of Confidence:" TARP, Presidential Rhetoric, and the Crisis of Neoliberalism. Issue 5 (20th October 2018) - Abbott, Blake
Abstract : This article analyzes the circulation of the term "confidence" as a prominent signifier for neoliberal logics, taking George W. Bush's response to the economic crisis in Fall 2008 as a case study. It traces the public circulation of confidence in previous presidential administrations and notes that much like previous administrations, Bush's response to the crisis was rooted in confidence. Bush identified a loss of confidence as the underlying cause of the economic crisis, and his focus on the need to restore lost confidence allowed him to violate his traditionally conservative principles in order to save the free market. Additionally, Bush's reliance on the term in the context of the economic crisis articulated the nation-state to the national economy through neoliberalism as a prevailing economic logic.